A web service model for schools information discovery - Afarasimu Auwalu Isah
Developing a model for schools information discovery is very important for information acquisition of schools. It would help users or stake holders to access the information of schools instantly. Nowadays most of Malaysian schools have their own website that published the information about the facilities, academic achievement and activities, co-curriculum programs, human resource and other resources. For the purpose of schools quality evaluation, parents and stakeholders always used the website for acquiring information regarding to schools performance, academic achievement, resources and facilities. Currently, there are limited studies or model that provides information discovery. The web service technology has been accepted generally as an appropriate method for discovering information from websites. It is the technology that can describe, communicate and manage different services over the Internet. This study aims to develop a new web service platform model for information discovery from various websites of the schools. The scope of discovery includes the information of schools facilities, curriculum offered and students' population. The proposed model is developed using Java Web Services platform. There are 15 different websites of the schools were used in the experiment. To simplify the discovery process, these websites are converted into an Extensible Markup Language (XML) format. The XML format is parsed into XMLDOM through XMLPARSER. Based on the XMLDOM, a keyword extraction based algorithm (KEA) is developed for extracting the classification attributes in the XMLDOM. The Application Program Interface (API) called as XMLHttpRequest object is used for receiving and reloading the data from the user terminal to the server. Meanwhile, the style sheet languages HTML and CSS are applied for displaying the results to the user. The results of the study showed that the proposed model is able to extract over 95% of required information related to the selected schools' websites. The contributions of this study can help users and stakeholders to discover the schools data instantly, instead of searching through each websites of the schools, which also save the users' time and resources.